The current framework of Development Education in Spain: achievements and challenges - Sarah CARRICA-OCHOA; Aurora BERNAL-MARTÍNEZ-DE-SORIA (Revista Iberoamericana de Estudios de Desarrollo)
Development Education (DE) has been gaining its own identity in Spain. The practice started in the context of NGOD, a context in which not only is DE still actively present, but also one in which it exerts considerable influence. DE has been reclaiming its own space and rationale and managing to find its way into all the educational contexts. But for this process to continue there should be institutional support translated into legislation which promotes its implementation. In this article we shall first study the principal conceptualization of DE in Spain and give a brief historical overview. In the second part the major milestones of DE will be highlighted in both non-formal and formal contexts. Namely, we shall look in more detail at the legislation which has enabled progress for DE.